(untitled) (مجلة المنصور, 2022)
Business Scheduling is a process for formulating a short-term plan, including timing of the tasks completion for a specific system, according to a limited sequence that allows the organization to achieve its targets in a perfect time .To do this is to deal with several methods the most recently of which is using algorithms . One of these methods is A.C.O of which that is used to solve the fusion problems, depending on the social behavior of ant, to ensure that A.C.O is the more better algorithms that are used to solve problems In the service system of the Neuroscience Hospital which distributes the patients to diagnosis devices to serve them in an ideal time. A.C.O compared with the most famous algorithms (G.A) by simulating the problems in terms of computerizing both algorithms. It has been found that the A.C.O is the better. Depending on above, and submitting real data from hospital we reached to more better business series total time (Make Span) as less as possible with activate less delay time for patients .